2022
DOI: 10.3390/molecules27123954
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Salicylates and Flavonoids in Poplar Bark and Leaves Based on IR, NIR, and Raman Spectra

Abstract: Poplar bark and leaves can be an attractive source of salicylates and other biologically active compounds used in medicine. However, the biochemical variability of poplar material requires a standardization prior to processing. The official analytical protocols used in the pharmaceutical industry rely on the extraction of active compounds, which makes their determination long and costly. An analysis of plant materials in their native state can be performed using vibrational spectroscopy. This paper presents fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 54 publications
(66 reference statements)
0
2
0
1
Order By: Relevance
“…A broad band of medium intensity, with a maximum at 6737 cm −1 , can be attributed to the first overtone of the hydroxyl group stretching vibrations and those located at around 6000 cm −1 to the first overtones of the ν(C–H) vibrations. In the 4800–4890 cm −1 frequency range, combination bands of ν(O–H) and ν(C=C) stretching vibrations are present [ 44 , 45 , 46 , 47 ]. In the NIR difference spectrum of the hydrated and anhydrous forms of diosmin, bands that can be attributed to the vibrations of the water molecule bonded to the diosmin carbohydrate fragment are observed at 4490 and 6950 cm −1 [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…A broad band of medium intensity, with a maximum at 6737 cm −1 , can be attributed to the first overtone of the hydroxyl group stretching vibrations and those located at around 6000 cm −1 to the first overtones of the ν(C–H) vibrations. In the 4800–4890 cm −1 frequency range, combination bands of ν(O–H) and ν(C=C) stretching vibrations are present [ 44 , 45 , 46 , 47 ]. In the NIR difference spectrum of the hydrated and anhydrous forms of diosmin, bands that can be attributed to the vibrations of the water molecule bonded to the diosmin carbohydrate fragment are observed at 4490 and 6950 cm −1 [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…The flavonoid profiles visualized by hierarchical cluster analysis indicated that Populus has a different flavonoid composition from Ficus carica L. and Actinidia arguta . Moreover, the flavonoid composition and contents vary among poplar species and clones ( Donaldson et al., 2006 ; Pobłocka-Olech et al., 2021 ; Mazurek et al., 2022 ). Thus, we propose that red poplar varieties may be useful as models for studying flavonoids in trees.…”
Section: Discussionmentioning
confidence: 99%
“…В народной медицине применяются различные виды сырья осины обыкновенной (листья, почки) в качестве противовоспалительного, противомикробного и спазмолитического средства. В экспериментальной медицине установлено, что кора осины обладает противовоспалительным действием, связывают это со способностью влиять на антиоксидантный статус организма [8].…”
unclassified